The Epidemiology of Cirrhosis in the United States: A Population-based Study - Scaglione, Steven; Kliethermes, Stephanie; Cao, Guichan; Shoham, David; Durazo, Ramon; Luke, Amy; Volk, Michael L (Journal of clinical gastroenterology, 2015)
Liver cirrhosis is an important public health concern in the United States and a significant source of morbidity and mortality. However, the epidemiology of cirrhosis is incompletely understood. The aims of this study were to estimate the prevalence of cirrhosis in the general US population, determine characteristics of affected Americans with a focus on health disparities, and calculate excess mortality attributable to cirrhosis. National Health And Nutrition Examination Survey data conducted between 1999 and 2010 were used to estimate cirrhosis prevalence and factors associated with cirrhosis. The National Center for Health Statistics-linked death certificate data from the National Death Index were linked to the National Health And Nutrition Examination Survey database for the years 1999 to 2004, and attributable mortality was calculated using propensity score adjustment. Cirrhosis was ascertained by aspartate aminotransferase-to-platelet ratio of >2 and abnormal liver function tests. The prevalence of cirrhosis in the United States was approximately 0.27%, corresponding to 633,323 adults. Sixty-nine percent reported that they were unaware of having liver disease. The prevalence was higher in non-Hispanic blacks and Mexican Americans, those living below the poverty level, and those with less than a 12th grade education. Diabetes, alcohol abuse, hepatitis C and B, male sex, and older age were all independently associated with cirrhosis, with a population attributable fraction of 53.5% from viral hepatitis (mostly hepatitis C), diabetes, and alcohol abuse. Mortality was 26.4% per 2-year interval in cirrhosis compared with 8.4% in propensity-matched controls. The prevalence of cirrhosis is higher than previously estimated. Many cases may be undiagnosed, and more than half are potentially preventable by controlling diabetes, alcohol abuse, and viral hepatitis. Public health efforts are needed to reduce this disease burden, particularly among racial/ethnic minorities and individuals at lower socioeconomic status.